Vigor of peristalsis during multiple rapid swallows is inversely correlated with acid exposure time in patients with NERD. Issue 2 (11th December 2015) - Martinucci, I.; Savarino, E. V.; Pandolfino, J. E.; Russo, S.; Bellini, M.; Tolone, S.; Tutuian, R.; Roman, S.; Furnari, M.; Frazzoni, M.; Macchia, L.; Savarino, V.; et al.
Abstract: Background: Multiple rapid swallowing (MRS) during high‐resolution manometry (HRM) is increasingly utilized as provocative test to assess esophageal peristaltic reserve. The aim of this study was to evaluate the correlation between MRS response and impedance and pH (MII‐pH) parameters in endoscopy negative heartburn (ENH) patients. Methods: We enrolled consecutive ENH patients, who underwent HRM and MII‐pH study, with a selected MII‐pH profile: abnormal MII‐pH (pH+/MII+); normal MII‐pH (pH−/MII−). HRM was performed with 10 wet swallows (WS) and one MRS. Mean distal contractile integral (DCI) during WS and MRS were calculated. MII‐pH parameters including acid exposure time (AET), reflux events, baseline impedance levels (BI) and the efficacy of chemical clearance evaluated with the postreflux swallow‐induced peristaltic wave (PSPW) index were measured. Key Results: We analyzed 103 patients: 49 MII+/pH+ (27 male), and 54 MII−/pH− (19 male). Mean age was similar between the two groups. As expected, mean AET and number of refluxes were higher in pH+/MII+ ( p < 0.05). HRM was normal in all selected patients. Mean DCI‐WS was similar between two groups ( p = n.s.). Mean DCI‐MRS‐ was higher in MII−/pH− vs MII+/pH+ ( p < 0.05). The increase in DCI‐MRS was inversely correlated with AET (−0.699; p < 0.001) and directly correlated with BI values (0.631; p < 0.001) and PSPW index (0.626; p < 0.001). Conclusions & Inferences: Following MRS, patients with abnormal impedance‐pH test showed suboptimal contraction response as compared with those with normal impedance‐pH test. Moreover, MRS response was inversely correlated with AET and directly correlated with BI values and PSPW index. Abstract : We evaluate two different groups of endoscopy negative heartburn patients that were classified with impedance and pH test in: pH+/MII+ and pH−/MII−. They underwent high‐resolution manometry with low volume multiple rapid swallow (MRS). The main results of our study were the following: (i) post‐MRS contractile DCI and MRS/WS ratio were lower in MII+/pH+ patients as compared with MII−/pH− (considered as control group); (ii) an inverse correlation between esophageal motor response after DCI‐MRS and MRS/WS ratio with AET was found; (iii) a direct correlation between DCI‐MRS and MRS/WS ratio with BI values and PSPW index were observed.